Gender and the Business Environment for New Firm Creation - Klapper, Leora F. (World Bank, 2013)
The authors summarize the extant literature on the relationship between gender and entrepreneurship. They note significant quantitative gender differences in business entry, with male-owned firms heavily prevailing over firms owned by women in many parts of the world. They find that enterprises owned by men on the one hand and women on the other are generally concentrated in different sectors, women entrepreneurs being better represented in labor intensive sectors such as trade and services rather than capital intensive manufacturing industries. They also observe certain gender differentials in business survival and growth patterns. Yet an analysis of a large body of literature does not suggest that, in general, the so called “gender gap” in entrepreneurship can be explained by explicit discrimination in laws or regulations. Rather, differences in quantitative and qualitative indicators of business entry and performance can in part be explained by a number of business environment factors that disproportionately affect a woman's decision to operate a business in the formal sector. For example the concentration of women in low capital intensive industries—which require less funding and at the same time have a lower potential for growth and development—might also be driven by barriers against women regarding access to finance. Furthermore, women may have relatively less physical and “reputational” collateral than men, which limits their access to finance. Overall the literature suggests that improvements in the business environment can help promote high-growth female entrepreneurship.